Resistance to imatinib in a ETV6::PDGFRB rearranged myeloid/lymphoid neoplasm with high-risk mutations: a case report - Cavelier, Lucia; Saft, Leonie; Sander, Birgitta; Deneberg, Stefan (Frontiers in Oncology, 2025)
Platelet-derived growth factor receptor beta (PDGFRB)-rearranged myeloid/lymphoid neoplasms (MLNs) are rare hematologic malignancies typically responsive to tyrosine kinase inhibitors (TKIs) such as imatinib. However, resistance—particularly in the context of co-occurring high-risk mutations—is uncommon and poorly characterized. We report a case of a 65-year-old man diagnosed with a ETV6::PDGFRB-translocated MLN, presenting as atypical chronic myeloid leukemia (aCML), who exhibited a brief response with development of resistance to imatinib. Although the patient initially achieved hematologic and partial cytogenetic remission, residual fibrosis and cytogenetic abnormalities persisted despite dose escalation. Molecular profiling revealed high-risk mutations in ASXL1, KRAS, NRAS, SETBP1, and SRSF2, along with a variant of uncertain significance (VUS) in IDH2. The patient progressed to acute myeloid leukemia (AML) within 11 months despite sequential therapies including dasatinib and azacitidine-venetoclax, ultimately succumbing to sepsis. This case highlights the limitations of TKI monotherapy in MLNs with PDGFRB rearrangements and co-existing high-risk mutations, underscoring the importance of early molecular profiling and consideration of allogeneic hematopoietic stem cell transplantation in cases with poor risk features.